2019
DOI: 10.1002/ejic.201900816
|View full text |Cite
|
Sign up to set email alerts
|

Allyl Complexes of Tungsten from the Rearrangement of Transient Cyclopropyl Precursors

Abstract: This article explores the contrasting reactivity of cyclopropyl complexes of early transition metals. [Cp*W(NO)(CH2R)(c‐C3H5)] (R = SiMe3, Ph, t‐Bu) generated in THF solution from [Cp*W(NO)(CH2R)Cl] and [Mg(c‐C3H5)2(dioxane)x] readily rearrange to η3‐allyl derivatives [Cp*W(NO)(CH2R)(η3‐C3H5)] by an intramolecular ring opening reaction. Both direct and catalyzed pathways are revealed by kinetic studies. Computational modeling indicates the ring opening reaction is preferred on thermodynamic grounds for tungste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…This step is not ac anonical b-carboelimination, but instead consists of adistal opening of the cyclopropyl ring (C•••C bond distance of 2.10 in TS2' '' '), ap rocess reminiscent to that previously proposed for cyclopropyl Rh III complexes and other transition metal derivatives. [25] Although the pathways proceeding through TS1 and TS1' ' cannot be discarded, the high stability of INT0' ',a nd Interestingly,t he computational study showed that the cyclopropyl to p-allyl rearrangement is also viable using an homologous Rh I complex (difference in activation barriers of approx. 1kcal mol À1 ).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…This step is not ac anonical b-carboelimination, but instead consists of adistal opening of the cyclopropyl ring (C•••C bond distance of 2.10 in TS2' '' '), ap rocess reminiscent to that previously proposed for cyclopropyl Rh III complexes and other transition metal derivatives. [25] Although the pathways proceeding through TS1 and TS1' ' cannot be discarded, the high stability of INT0' ',a nd Interestingly,t he computational study showed that the cyclopropyl to p-allyl rearrangement is also viable using an homologous Rh I complex (difference in activation barriers of approx. 1kcal mol À1 ).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…This step is not ac anonical b-carboelimination, but instead consists of adistal opening of the cyclopropyl ring (C•••C bond distance of 2.10 in TS2' '' '), ap rocess reminiscent to that previously proposed for cyclopropyl Rh III complexes and other transition metal derivatives. [25] Although the pathways proceeding through TS1 and TS1' ' cannot be discarded, the high stability of INT0' ',a nd especially,t he low activation barriers associated with the subsequent steps,c learly favor the mechanism involving the cobaltacyclopentene INT1' '' '.…”
Section: Resultsmentioning
confidence: 99%
“…Deuterated solvents (benzene- d 6 , toluene- d 8 , cyclohexane- d 12 ) were degassed by freeze–pump–thaw cycles, dried over activated molecular sieves, and stored under argon. The syntheses of complex 1 , cyclopropyllithium, dicylopropylmagnesium, , dicyclopropylzinc, were carried out according to the reported procedures with limited modifications. Tricyclopropylaluminum was synthesized following a modified procedure used for triphenylaluminum …”
Section: Methodsmentioning
confidence: 99%